Health management of beef cattle: A case study - Hartady, Tyagita; Widyastuti, Rini; Hiroyuki, Andi (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2021)
The reports about how are farmers able to prevent, identify and treat the animal diseases to not get worse while the production is still maintained, are limited. The application of the standard good farming practices is also not well documented. Therefore, to provide adequate information about beef cattle health management in smallholders, especially in Indonesia; this study was conducted at "Putra Nusa " Beef Cattle Group, located in Kalensari Hamlet, Kondangjajar Village, Cijulang District, Pangandaran Regency. The study was carried out by survey and observation to determine the farmers' level of knowledge about health, care and treatment of beef cattle. The result showed that farmers do not have a background in animal health, resulting in a lack of knowledge about beef cattle health management. Most breeders rely on natural ingredients to treat sick animals. Farmer's concern about vaccination and routine anthelmintic administration was only about 15% and 22%, respectively, contributed to the increase of helminthiasis cases (45%). Improve the knowledge about cattle diseases supported by the easy access to veterinarian will minimize the losses of breeders.